RELEVANSI TAFSIR AL-IBRIZ DENGAN KOMIK SURGA DAN NERAKA KARYA MB. RAHIMSYAH - Farida Nur Afifah (Mafatih, 2022)
The picture of heaven and hell is a sure thing in Islam. Both studies received attention from mutakallimin people, especially in the doomsday concept. Visualization of heaven and hell in the Al-Qur’an becomes a problem that is often debated, because of its position which is ‘ghoib’. Its existence can only be interpreted according to human capability. This becomes interesting when visualized in a comic and consumed by various groups. This study is devoted to the book of interpretation of al-Ibriz, a book of the archipelago. To see the relevance between the meaning in al-Ibriz’s interpretation of books and comics, then this study was conducted. This study is library research, with thematic methods and interpretation of al-Ibriz as the object of study. Study sources are sought in various works of literature related to the theme of the discussion. The result of this research is that the visualization of heaven and hell in comics is in accordance with the Al-Qur’an. This is reviewed from various verses in the book of al-Ibriz interpretation that both have relief, although not all. Whit this visualization is expected to increase the faith and diversity of thinking in every action. Gambaran surga dan neraka merupakan suatu hal yang pasti dalam agama Islam. Kedua kajian tersebut mendapat perhatian dari kalangan mutakallimin khususnya dalam konsep kiamat. Visualisasi surga dan neraka dalam Al-Qur’an menjadi suatu masalah yang sering diperdebatkan, karena posisinya yang masih bersifat ghoib. Keberadaanya hanya bisa ditafsiri sesuai kemampuan manusia. Hal ini menjadi menarik ketika divisualisasikan dalam sebuah komik dan dikonsumsi oleh berbagai kalangan. Kajian ini dikhususkan pada kitab tafsir al-Ibriz, sebuah kitab Nusantara. Untuk melihat relevansi antara makna dalam kitab tafsir al-Ibriz dan komik, kemudian kajian ini dilakukan. Kajian ini berbentuk penelitian kepustakaan, dengan metode tematik dan tafsir al-Ibriz sebagai objek kajian. Sumber kajian dicari dalam berbagai literatur yang berkaitan dengan tema pembahasan. Adapun hasil dari penelitian ini adalah visualisasi surga dan neraka yang ada pada komik sudah sesuai dengan Al-Qur’an. Hal ini ditinjau dari berbagai ayat dalam kitab tafsir al-Ibriz bahwa keduanya memiliki kerelevensian, meskipun tidak semuanya. Dengan adanya visualisasi tersebut diharapkan dapat menambah keimanan dan kemajemukan berfikir pada setiap tindakan.